2018
DOI: 10.1002/pbc.26960
|View full text |Cite
|
Sign up to set email alerts
|

Specific expression of PD‐L1 in RELA‐fusion supratentorial ependymoma: Implications for PD‐1‐targeted therapy

Abstract: These findings in ST-RELA suggest tumor evasion and immunsuppression due to PD-L1/PD-1-mediated T-cell exhaustion. Trials of checkpoint inhibitors in EPN should be enriched for ST-RELA tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…Again, as previously mentioned, such a finding far from guarantees a response and in these landmark papers they found that even in patients that expressed PD-L1 on tumor cells, the response rate to the treatment was only 39% [44]. In addition, Witt et al [46] nicely demonstrated, using T cell exhaustion testing of various types of ependymomas, that elevated PD-L1 expression in tumors can be indicative of either tumor adaptations to hide from the innate immune response or due to normal T-cell antigen-activation, a known function of PD-1. In their study they utilized functional T cell exhaustion assays that stimulate T cells via exposure to Phorbol 12-myristate 13-acetate (PMA)/ionomycin.…”
Section: Immune Checkpoint Inhibitors and Their Potential Use In Acpmentioning
confidence: 89%
See 2 more Smart Citations
“…Again, as previously mentioned, such a finding far from guarantees a response and in these landmark papers they found that even in patients that expressed PD-L1 on tumor cells, the response rate to the treatment was only 39% [44]. In addition, Witt et al [46] nicely demonstrated, using T cell exhaustion testing of various types of ependymomas, that elevated PD-L1 expression in tumors can be indicative of either tumor adaptations to hide from the innate immune response or due to normal T-cell antigen-activation, a known function of PD-1. In their study they utilized functional T cell exhaustion assays that stimulate T cells via exposure to Phorbol 12-myristate 13-acetate (PMA)/ionomycin.…”
Section: Immune Checkpoint Inhibitors and Their Potential Use In Acpmentioning
confidence: 89%
“…They found that infiltrating T-cells in RELA fusion supratentorial ependymoma did not secrete IFN-gamma. They concluded that this suggested that in the case of RELA fusion ependymoma, the increased expression of PD-1/PD-L1 results in the exhaustion of infiltrating T-cells and immune evasion by the tumor [46]. On the contrary, they found that in group B ependymomas (which also express high levels of PD-1), infiltrating T-cells were, in fact, capable of secreting IFN-gamma after stimulation with PMA/ionomycin.…”
Section: Immune Checkpoint Inhibitors and Their Potential Use In Acpmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PD-1/PD-L1 axis influence the balance between tumor immune surveillance and immune resistance as well [ 12 , 13 ]. Elevated PD-L1 expression on tumor cell or tumor infiltrating lymphocyte (TIL) results in the exhaustion of T cell [ 14 ], thus the attenuated tumor-specific immunity promoting tumor progression [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…An oncogenic fusion of RELA with C11orf95 has been described in the majority of supratentorially located ependymoma, and supratentorial RELA ‐fused ependymoma (ST‐EPN‐RELA) was introduced as a separate entity in the 2016 World Health Organization (WHO) classification of CNS tumors . Although preclinical evidence exists on subgroup specific potential drugs, data on the clinical impact of the molecular diagnosis are rare and refer to heterogeneous, retrospective cohorts, with limited information on clinical staging and treatment . Previously described markers for risk association are gain of 1q, which was associated with poor prognosis in several cohorts, whereas histopathological grading could not be confirmed as a clinical prognostic marker .…”
Section: Introductionmentioning
confidence: 99%